AN OUTLINE OF VARIABLES IN PELLETIZATION BY EXTRUSION AND SPHERONIZATION - MISHRA, RAKESH V.; PALDEWAR, SHUBHAM G.; NANDGUDE, TANAJI D. (International Journal of Applied Pharmaceutics, 2020)
Pelletization is an agglomeration process which converts fine granules or powders of bulk drugs into small, free-flowing, spherical units, known as pellets. The pelletization can be achieved either through agitation, compaction (extrusion-spheronization), drug layering and globulation. Among the various pelletization techniques extrusion–spheronization process is preferred over other methods for the preparation of pellets as it allows the incorporation of the higher amount of drug, modified physical characteristics of the drug (density, sphericity, narrow size distribution, smoother surface) and multiple drugs can be easily combined in the same unit. This current review summarizes the findings or investigations by the researchers on various variables, including process parameters, equipment parameters and formulation parameters influencing the quality of pellets. The article also focuses on process optimization and additives used in pellets formulation. To prepare the current review search criterion used was the parameters affecting final pellet characterization in the extrusion spheronization process. The sources were peer-reviewed relevant scientific articles of recognized journals. Keywords used as filters were extrusion, spheronization, formulation parameters, process parameters, equipment parameters, moisture content, granulating liquid, drying rate, extrusion temperature, spheronizer load, pelletization. Literature survey has been done in a range of years (1992-2019) regarding the various variables of the extrusion spheronization process, which affects and has foremost impact on the final quality of pellets so as to make the review updated and comprehensive.